Simultaneous Determination of a Novel PD-L1 Inhibitor, IMMH-010, and Its Active Metabolite, YPD-29B, in Rat Biological Matrices by Polarity-Switching Liquid Chromatography-Tandem Mass Spectrometry: Application to ADME Studies - Jiang, Jianwei; Zou, Xiaowen; Liu, Yuke; Liu, Xiao; Dong, Kai; Yao, Xiaoqing; Feng, Zhiqiang; Chen, Xiaoguang; Sheng, Li; Li, Yan (Frontiers in Pharmacology, 2021)
IMMH-010 is a prodrug of YPD-29B, which is a novel PD-L1 inhibitor. A specific and sensitive LC-MS/MS method with polarity switching was developed and validated for the simultaneous determination of IMMH-010 and YPD-29B in rat plasma, liver, brain, urine and fecal samples. Method validation was investigated to demonstrate the lower limit of quantification linearity, precision and accuracy, matrix effect and recovery, stability and dilution reliability for IMMH-010 and YPD-29B. This validated method was successfully applied to investigate the pharmacokinetics, tissue distribution, and excretion of IMMH-010 and YPD-29B in rats. After oral administration of IMMH-010 maleate to rats, IMMH-010 was rapidly and extensively converted to the active metabolite YPD-29B. The areas under the plasma concentration-time curve (AUC) of IMMH-010 and YPD-29B were proportional to the dose in the range of 10–100 mg/kg. IMMH-010 was primarily distributed in the adrenal gland, lymph nodes, heart, liver and spleen. YPD-29B was mainly observed in the liver, lymph, kidney, and lung. Approximately 28.81% of the IMMH-010 dose was recovered in the urine and feces within 72 h, including unchanged IMMH-010 (7.99%) and YPD-29B (20.82%). The results of this study may be useful as a reference for further development of IMMH-010 and PD-L1 inhibitors. Clinical Trial Registration: [https://clinicaltrials.gov/ct2/show/NCT04343859?term=IMMH-010&draw=2&rank=1], identifier [NCT04343859]."